Removal of Polyvinyl Alcohol Using Photoelectrochemical Oxidation Processes Based on Hydrogen Peroxide Electrogeneration - Kai-Yu Huang; Chih-Ta Wang; Wei-Lung Chou; Chi-Min Shu (International Journal of Photoenergy)
This study investigates the removal efficiency of PVA from aqueous solutions using UV irradiation in combination with the production of electrogenerated hydrogen peroxide (H2O2) at a polyacrylonitrile-based activated carbon fiber (ACF) cathode. Three cathode materials (i.e., platinum, graphite, and ACF) were fed with oxygen and used for the electrogeneration of H2O2. The amount of electrogenerated H2O2 produced using the ACF cathode was five times greater than that generated using the graphite cathode and nearly 24 times greater than that from platinum cathode. Several parameters were evaluated to characterize the H2O2 electrogeneration, such as current density, oxygen flow rate, solution pH, and the supporting electrolyte used. The optimum current density, oxygen flow rate, solution pH, and supporting electrolyte composition were found to be 10 mA cm−2, 500 cm3 min−1, pH 3, and Na2SO4, respectively. The PVA removal efficiencies were achieved under these conditions 3%, 16%, and 86% using UV, H2O2 electrogeneration, and UV/H2O2 electrogeneration, respectively. A UV light intensity of 0.6 mW cm−2 was found to produce optimal PVA removal efficiency in the present study. A simple kinetic model was proposed which confirmed pseudo-first-order reaction. Reaction rate constant (kap) was found to depend on the UV light intensity.